Treatment Responses to Tooth Whitening in Twins. (16th January 2014) - Corby, Patricia M. A.; Biesbrock, Aaron; Gerlach, Robert; Corby, Andrea L.; Moreira, Alexandre; Schork, Nicholas J.; Bretz, Walter A.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this study was to determine heritability estimates of treatment responses to a 10% hydrogen peroxide strip-based whitening system in twins. Eighty-five twin pairs were randomly assigned to 10% hydrogen peroxide whitening strips or placebo strips without peroxide. Both twins (monozygotic or dizygotic) received the same treatment. Maxillary teeth were treated for 30 minutes twice daily for 7 days. Efficacy was measured objectively as L* (light–dark), a* (red–green), and b* (yellow–blue) color change from digital images at baseline (∆) and day 8. Heritability estimates for tooth whitening treatment responses for changes from day 8 to baseline were obtained using variance-component methodologies. Whitening treatment responses were highly heritable (h2 = 71.0) for ∆b* and ∆a*(p < .0001), but not for ∆L* (h2 = 27.0), which was essentially modulated by environmental factors. This study has demonstrated that both genetic and environmental factors significantly contributed to seven-day whitening treatment responses achieved with 10% hydrogen peroxide strips.